Encapsulated Fish Oil Products Available in the UK Meet Regulatory Guidelines With Respect to EPA + DHA Contents and Oxidative Status. Issue 10 (20th August 2018) - Sprague, Matthew; Cooper, Sean; Tocher, Douglas R.; Betancor, Mónica B.
Abstract : Encapsulated fish oil products continue to be of high interest, particularly concerning labeling claims and oxidative status. Thus, the present study analyzes 23 encapsulated fish oil products from the UK for their lipid and fatty acid composition as well as oxidation parameters. Oil contents range from 91.4% to 118.9% of the manufacturers' stated level. Lipid class analyses reveals three different types of oil products consisting of either triacylglycerol (TAG), ethyl ester (EE), or in combination (EE/TAG). Fatty acid profiles vary according to oil form with long‐chain omega‐3 fatty acids, eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), more concentrated in EE compared to TAG‐based oils with TAG/EE oils containing intermediary levels. Twelve products have EPA + DHA contents lower than advertised, although this is reduced to 11 when the actual measured capsule oil content is taken into consideration. All products have peroxide (PV) and anisidine values below those set by pharmacopeias, although four products have a PV above the industry set limit of 5 meq kg −1 . No relationships are found between oxidative parameters and missing EPA + DHA contents, although a significant relationship is observed between PV and days to expiry. In summary, encapsulated fish oil products on the UK market are not oxidized and meet regulatory guidelines with respect to EPA + DHA contents and oxidative status. Practical Applications : The study highlights the importance of quantifying the actual capsule oil content when determining EPA + DHA levels with respect to label claims. Furthermore, it also places results into context regarding regulatory guidelines demonstrating to regulatory bodies and consumers alike that UK fish oil products do meet specification and are not oxidized. The capsule oil content, lipid class composition, EPA+DHA content, and oxidative status of commercially available fish oil capsules are tested to see if products meet stated values and are not oxidized. The outcome shows that encapsulated fish oil products available in the UK do meet specification with regards to EPA+DHA levels and are not oxidized. Abstract : The capsule oil content, lipid class composition, EPA+DHA content, and oxidative status of commercially available fish oil capsules are tested to see if products meet stated values and are not oxidized. The outcome shows that encapsulated fish oil products available in the UK do meet specification with regards to EPA+DHA levels and are not oxidized.